Minimally invasive surgery versus open gastrectomy for older patients with gastric cancer: A propensity score‐matching analysis - Masaaki Yamamoto; Takeshi Omori; Yasunori Masuike; Naoki Shinno; Hisashi Hara; Takahito Sugase; Takashi Kanemura; Atsushi Takeno; Motohiro Hirao; Hiroshi Miyata (Annals of Gastroenterological Surgery)
Abstract Aim To compare minimally invasive and open surgery for older patients with gastric cancer. Methods This study included 464 consecutive patients with gastric cancer aged ≥75 years who underwent open or laparoscopic gastrectomy at our institution from January 2004 to December 2018. We performed propensity score‐matching and compared short‐ and long‐term outcomes between the two groups. Results After matching, 332 patients were included in the study (166 in each group). The laparoscopy group had a longer operative time, lesser blood loss, and shorter hospital stays than the open surgery group (all p < 0.020). The laparoscopy group had a lower complication rate than the open surgery group (p = 0.002). No significant differences were noted in the 3‐y overall, recurrence‐free, and disease‐free survival between the groups (all p > 0.200). Conclusion Minimally invasive surgery for older patients with gastric cancer may be more beneficial than open gastrectomy in terms of blood loss and hospital stay.